2018
DOI: 10.1186/s12889-018-6033-1
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal observation study assessing changes in indicators of serious injury and violence with alcohol controls in four remote indigenous Australian communities in far north Queensland (2000–2015)

Abstract: BackgroundLegal restrictions on alcohol availability have been used to address violence and injury in the world’s remote Indigenous communities. In Australia, alcohol management plans (AMPs) were implemented by the Queensland Government in 2002. This study reports changes in indicators of alcohol-related violence and injury in selected communities.MethodsDesign and setting: A longitudinal observational study was conducted in four Aboriginal and Torres Strait Islander (Indigenous) communities in Cape York, far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Although it is not possible to establish a causal link from our data, cannabis [37] and alcohol have both indirect and direct mental health effects. In terms of the former, both result in major resource diversion in these welfare-dependent sustenance economies with alcohol, in particular, associated with violence [38], powerfully compromising the stability of the neurodevelopmental environment. Further, cannabis use during adolescence is associated with an increased risk of psychosis [39], and cannabis-induced psychosis can convert to schizophrenia, with highest risk for those aged 16–25 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not possible to establish a causal link from our data, cannabis [37] and alcohol have both indirect and direct mental health effects. In terms of the former, both result in major resource diversion in these welfare-dependent sustenance economies with alcohol, in particular, associated with violence [38], powerfully compromising the stability of the neurodevelopmental environment. Further, cannabis use during adolescence is associated with an increased risk of psychosis [39], and cannabis-induced psychosis can convert to schizophrenia, with highest risk for those aged 16–25 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of AMPs the overall rate of assault, serious injury and aeromedical retrieval from these communities has fallen significantly 9,23 . Nevertheless, several authors have recently reported the rates of assault, 10 traumatic brain injury 11 and aeromedical retrieval 10 are gradually rising towards pre‐2008 levels. The results of our study indicate there has been a significant decline in the incidence of ocular trauma in the Cape York and Torres Strait Island Indigenous communities since the implementation of AMPs, thus supporting this health policy as a preventative strategy.…”
Section: Discussionmentioning
confidence: 99%
“…While the rate of serious injury requiring aeromedical retrieval from FNQ Indigenous communities had fallen significantly until 2010, 9 robust conclusions regarding the sustained effectiveness of AMPs have been guarded. Rates of assault, 10 traumatic brain injury 11 and aeromedical retrieval 10 have been slowly rising since the reported nadir in 2010. This study aimed to review the epidemiology of ocular trauma admitted to Cairns Hospital from the FNQ health districts in the period following the implementation of AMPs in Indigenous Communities.…”
Section: Introductionmentioning
confidence: 99%
“…This is despite alcohol restrictions being in place in many of the remote communities which, as evidence shows, reduced violence and serious injury generally in these communities (Margolis et al 2011 ). However, recent evidence suggests that the positive effects of these restrictions are reversing (Clough et al 2018 ), making it essential to examine the possible impacts on TBI rates in more detail. We also found interesting patterns in incidence rates that clearly need further research.…”
Section: Discussionmentioning
confidence: 99%